Developing Early Childhood Reading Skills Through Smart Box Media in Group B at KB Rinjani - Suryanirmala, Neni; Arfini, Baiq Desi; Haeri, Zul (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Beginning reading skills need to be stimulated from an early age so that children do not experience many difficulties in studying various fields of study at the next level of education. This research aims to improve the initial reading ability of smart box media in group B at Rinjani KB. The type of research used in this research is collaborative Classroom Action Research which uses the Kemmis and Mc Taggart model. The subjects of this research were 13 group B children at Rinjani KB. Data collection methods are carried out through observation and documentation. The data analysis technique was carried out descriptively quantitatively. The research results show that children's initial reading abilities can be improved using smart box media. The increase in initial reading ability can be seen based on the percentage increase from pre-action of 0% to an increase of 7.96%. In cycle I it was 7.96%, in cycle II it increased from 76.93% to 84.62% with the criteria of developing very well.